2021
DOI: 10.1111/apa.15857
|View full text |Cite
|
Sign up to set email alerts
|

Supporting parents as essential care partners in neonatal units during the SARS‐CoV‐2 pandemic

Abstract: Aim: To review the evidence on safety of maintaining family integrated care practices and the effects of restricting parental participation in neonatal care during the SARS-CoV-2 pandemic. Methods: MEDLINE, EMBASE, PsycINFO and CINAHL databases were searched from inception to the 14th of October 2020. Records were included if they reported scientific, empirical research (qualitative, quantitative or mixed methods) on the effects of restricting or promoting family integrated care practices for parents of hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 23 publications
(87 reference statements)
6
75
0
1
Order By: Relevance
“…COVID‐19 has starkly demonstrated the negative impact of parent‐infant separation in the NICU. In response The International FICare Steering Committee has developed recommendations highlighting the urgent, universal need to support all parents to be present continuously, routinely leading and participating in neonatal care and decision making for their child 36 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID‐19 has starkly demonstrated the negative impact of parent‐infant separation in the NICU. In response The International FICare Steering Committee has developed recommendations highlighting the urgent, universal need to support all parents to be present continuously, routinely leading and participating in neonatal care and decision making for their child 36 …”
Section: Discussionmentioning
confidence: 99%
“…The COVID‐19 pandemic highlighted the vulnerability within programs supporting parental presence in neonatal units. As hospitals attempted to decrease the risk of exposure to patients, policies limiting parent access were implemented; creating adverse effects on delivery of neonatal care, and outcomes for infants and families 36 . Despite longstanding public pledges by healthcare organizations to deliver family‐centered care, often they did not involve families in the development of COVID‐19 pandemic response plans 37…”
Section: Sustaining Ficarementioning
confidence: 99%
See 1 more Smart Citation
“…Recent research demonstrates that the COVID-19 pandemic and related restrictions are affecting both provision and quality of neonatal care [4] with a severe impact on infant and family-centred developmental care (IFCDC) [ 6 , 8 ]. Few studies have been conducted focusing on how the mother's presence with the newborn, frequency of parental presence, and developmental care practices have been influenced [ 5 , 9 , 10 ], or mothers’ experiences on receiving support for breastfeeding during lockdown [11] .…”
Section: Introductionmentioning
confidence: 99%
“…
A review of data from 286 neonatal units around the world showed that changes introduced during the COVID‐19 pandemic restricted how parents could care for their preterm infants 8 . This had a negative impact on breastfeeding, attachment, the parents’ mental health and staff stress levels.…”
Section: Long Covid In Children and How Pandemic Restrictions Affected Preterm Infantsmentioning
confidence: 99%